Antimicrobial activity of Lippia sidoides Cham. (Verbenaceae) essential oil against Staphylococcus aureus and Escherichia coli Atividade antimicrobiana do óleo essencial de Lippia sidoides Cham. (Verbenaceae) contra Staphylococcus aureus e Escherichia coli - C.E Castro; J.M Ribeiro; T.T Diniz; A.C Almeida; L.C Ferreira; E.R Martins; E.R Duarte (Universidade Estadual Paulista, 2011)
The antibacterial effect of Lippia sidoides (rosemary pepper) essential oil was tested against the bacteria Staphylococcus aureus and Escherichia coli isolated from homemade Minas cheese produced in Brazil. The Minimum Inhibitory Concentration (MIC) determined in the Dilution Test was 13 µL oil mL-1 for both bacteria, which characterizes inhibitory action in broth for a 24-hour interaction period. The Minimum Bactericidal Concentration (MBC) determined in the Suspension Test, with one minute of contact, was 25 µL oil mL-1 for both tested bacteria, obtaining at this concentration a bactericidal effect of 99.9% on the viable bacterial cells from each sample. Results demonstrated the bacterial activity of Lippia sidoides essential oil against S. aureus and E. coli, suggesting its use as an antibacterial agent in foods. O efeito antibacteriano do óleo essencial da Lippia sidoides (alecrim-pimenta) foi testado contra as bactérias Staphylococcus aureus e Escherichia coli isoladas de queijo minas artesanal, produzido no Brasil. A Concentração Inibitória Mínima (CIM) determinada por Teste de Diluição foi de 13 µL de óleo mL-1 para as duas bactérias, o que caracteriza ação inibitória em caldo durante vinte quatro horas de interação. A Concentração Bactericida Mínima (CBM) determinada através de Teste de Suspensão, com um minuto de contato, foi de 25 µL de óleo mL-1 para ambas as bactérias testadas, obtendo-se a esta concentração o efeito bactericida de 99,9% sobre as células bacterianas viáveis em cada uma das amostras. Os resultados demonstraram atividade bactericida do óleo essencial de Lippia sidoides contra S. aureus e E. coli, sugerindo a possibilidade do uso como agente antibacteriano em alimentos.